South American fish species suitable for aquaponics: a review - Pinho, Sara M. [UNESP]; David, Luiz H. [UNESP]; Garcia, Fabiana [UNESP]; Keesman, Karel J.; Portella, Maria Célia [UNESP]; Goddek, Simon (Springer Nature, 2021)
Tilapia and catfish are the most popular fish species in aquaponics. However, they are not well-accepted in all markets, and finding alternative species is important in order to increase the variety of food products and meet market demands. South America has several potential fish species for aquaponics systems. Encouraging the implementation of integrated aquaculture systems by providing information about the production of South American species can help to increase the supply of high-quality food and aquaculture diversification. Thus, data for five South American fish species with potential for aquaponics were compared with existing data for the main traditional warm water species in this system, tilapia and catfish. Moreover, the degree of suitability of the novel species for these systems in terms of zootechnical performance, tolerance to water quality and nutritional composition of fish flesh were discussed. The South American species considered were jundia or silver catfish (Rhamdia quelen), yellowtail lambari (Astyanax lacustris), pacu (Piaractus mesopotamicus), tambaqui (Colossoma macropomum) and snook (Centropomus spp.). Their description and the tabular comparison with the most traditional aquaponic-cultured species show they are suited for this production system. How suitable they are will depend on the system design, as well as the regional characteristics of the market where they will be produced.
Keywords: Aquaculture diversification; Aquaponics; Food security; Integrated food production